Джерела вивчення діяльності національно-культурних товариств Волині у першій третині ХХ століття - Булавіна, С.; Bulavina, S. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
У статті проаналізовано джерельну базу, яка дозволяє вивчити діяльність національно-культурних товариств Волині в першій третині ХХ ст., та з'ясовано, що означена проблема цікавила й українських, і польських науковців. Історичний шлях Західної України у складі Польської держави протягом 20-30-х років XX ст. був своєрідним, важким і суперечливим. Українське населення краю зазнавало національного та соціального гноблення з боку властей, насамперед це стосувалося сфери освіти та культури. Вивченням історії освіти та культури в Західній Україні, зокрема й на Волині, займалися педагоги, публіцисти, громадські діячі. Але й до сьогодні відсутні комплексні дослідження, присвячені діяльності українських культурно-освітніх товариств на Волині в першій третині ХХ ст. The article analyzes the source basis allowing to study the activities of national-cultural societies in Volyn in early XX-th cent. It has been proved that above-mentioned problem attracted both Ukrainian and Polish scholars. The historical development of Western Ukraine, as a part of the Polish state in 20-30-ies of XX-th cent., was peculiar, hard and controversial. Ukrainian population suffered of national and social oppression from the authorities especially in the sphere of culture and education. Prominent educationalists, public activists, journalists studied the history of education and culture of Western Ukraine and, primarily, those of Volyn. The author states that there is a lack of complex investigations devoted to the activities of the Ukrainian cultural-educational societies in Volyn in early XX-th cent. Modern scientific studies, using rich source and methodological basis, represent the objective picture of Ukrainian societies’ activities. The results of these studies make it possible to trace the main landmarks of the societies’ formation and development and their importance for the social-political and cultural life of Volyn.
Sources of Investigating the Activities of National-cultural Societies in Volyn in Early XX-th cent.
Keywords: національно-культурні товариства; джерельна база; Польська держава; архівні матеріали; документи; освіта; культура; мова; Західна Україна; Волинь; National-cultural societies; source basis; Polish state; archive materials; documents; education; culture; language; Western Ukraine; Volyn